CREATIVITY IS EVERYONE’S BUSINESS: HOW TO ENHANCE EMPLOYEE CREATIVITY IN TELECOMMUNICATION SECTOR - KARIM SEHRISH; SARFRAZ UMER (Annals of the University of Oradea: Economic Science, 2016)
With rapid cultural, demographical and economic changes in knowledge oriented economy, employee creativity has become a challenge for organizations, as this works as a core competence. We suggest that leaders with ethical commitment help to nourish creativity in employees. Using social learning theory, authors examined the influence of ethical leadership on employee creativity through the mediation of self-efficacy. This study also explored the moderating role of uncertainty avoidance between the relationship of ethical leadership and employee creativity. Data was collected from 180 employees along with their supervisors from four different telecommunication companies working in Pakistan. The questionnaire was adopted and tested on the criteria of five point Likert scale. Regression and Correlation tests were used to check hypothesis. Supervisors of these four companies evaluated the creativity of the selected staff member groups while the employees and staff members reported the perceptions about their supervisors in terms of ethical leadership. Results showed that ethical leadership was positively related to employee creativity and this relationship was mediated by self-efficacy and this mediation was partial. There was significant negative relationship between uncertainty avoidance and employee creativity, this is the main aspect of present study. According to the results uncertainty is negatively associated with the employee creativity it means high uncertainty results in low creativity of employees. This study was conducted in Pakistani context where uncertain attitude is very common in society so uncertainty avoidance affects creativity of the employee in Pakistani organizations. Our study offer practical implications for telecommunication companies in order to achieve competitive advantage by enhancing employee creativity, as employee creativity makes organization creative.